1990
DOI: 10.1099/00221287-136-11-2149
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of calcium, calmodulin and protein phosphorylation in morphogenesis of Candida albicans

Abstract: N-Acetyl-D-glucosamine-induced germ tube formation in Candda albicans at 37°C was accompanied by an increase in the rate of protein phosphorylation. The calmodulin antagonist trifluoperazine and the Ca2+ ionophore A23187, which inhibited germ tube formation, also reduced the rate of phosphorylation. The rate of phosphorylation was also reduced when cells were incubated at 25 "C, which favoured yeast-phase growth. Twodimensional SDS-PAGE analysis of phosphoproteins from germ-tube-forming and yeast cells reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 34 publications
(29 reference statements)
2
23
0
1
Order By: Relevance
“…Whether this involves novel signaling mechanisms specific to germ tube formation or the fine-tuning of a calmodulindependent protein kinase pathway has yet to be determined. Consistent with the latter hypothesis, Paranjape et al (23) detected at least twice as much calmodulin activity, measured by the capacity of extracts to stimulate cyclic AMPphosphodiesterase, in germ tube-forming/hyphal cells as in yeast cells. Since the germ tube may facilitate nutrient scavenging through directional growth, limiting ATPase activity by ATP availability (KO.5 for Mg-ATP is 2 mM) rather than by the product of a single metabolic substrate such as glucose may be an advantage.…”
Section: Discussionsupporting
confidence: 57%
“…Whether this involves novel signaling mechanisms specific to germ tube formation or the fine-tuning of a calmodulindependent protein kinase pathway has yet to be determined. Consistent with the latter hypothesis, Paranjape et al (23) detected at least twice as much calmodulin activity, measured by the capacity of extracts to stimulate cyclic AMPphosphodiesterase, in germ tube-forming/hyphal cells as in yeast cells. Since the germ tube may facilitate nutrient scavenging through directional growth, limiting ATPase activity by ATP availability (KO.5 for Mg-ATP is 2 mM) rather than by the product of a single metabolic substrate such as glucose may be an advantage.…”
Section: Discussionsupporting
confidence: 57%
“…The C-terminal half of the Na + \H + antiporters is less conserved and varies in length, and is speculated to play a regulatory role (Aronson et al, 1982 ;Balcells et al, 1997 ;. Studies of the mammalian Na + \H + antiporter family (NHE1-NHE6) also revealed the existence in the Cterminal tail of consensus sites for phosphorylation by protein kinase A and\or protein kinase C as well as sites suitable for calmodulin kinases and for proline-directed Ser\Thr kinases (Paranjape et al, 1990 ;Padan & Schuldiner, 1994). Regulated phosphorylation of NHE1 and NHE3 have been experimentally demonstrated (Bianchini et al, 1997 ;Wakabayashi et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin has been detected in a range of filamentous and dimorphic fungi, and yeasts from diverse taxonomic groups (Gomes et al, 1979;Grand etal., 1980;Hubbard et al, 1982;Cox et al, 1982;Salgado-Rodriguez et al, 1986;Muthukumar et al, , 1986Muthukumar et al, , 1987Laccetti et al, 1987). A Ca2+-calmodulin interaction has previously been reported to be necessary for germ tube and mycelial development in Ceratocystis ulmi (Muthukumar & Nickerson, 1984 and Candida albicans (Sabie & Gadd, 1989) probably through calmodulin-dependent protein phosphorylation (Roy & Datta, 1987;Paranjape et al, 1990), as in the entomopathogen Metarhizium anisopliae (St Leger et al, 1989 and Zoophthora radicans (Magalhiies et al, 1991). More recently, indirect evidence has been presented for the existence of an inositol lipid signalling system, which may effect elevation of intracellular [Ca2+], (Berridge & Irvine, 1984), in 0. ufmi (Brunton & Gadd, 1991).…”
Section: Introductionmentioning
confidence: 99%